A Rapid and Efficient Self‐Healing Thermo‐Reversible Elastomer Crosslinked with Graphene Oxide. (15th August 2013) - Wang, Chao; Liu, Nan; Allen, Ranulfo; Tok, Jeffrey B.‐H.; Wu, Yunpeng; Zhang, Fan; Chen, Yongsheng; Bao, Zhenan
<x xml:space="preserve">Abstract</x> A self‐healing thermo‐reversible elastomer is synthesized by cross‐linking a hydrogen bonding polymer network with chemically‐modified graphene oxide. This nanocomposite allows for both rapid and efficient self‐healing (in only several minutes) at room temperature, without the need for any external stimuli (e.g., heating or light exposure), healing agents, plasticizers or solvents. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>